Iron-assisted biological wastewater treatment: Synergistic effect between iron and microbes - Tian, Tian; Yu, Han-Qing (Biotechnology advances, 2020)
Iron-assisted biological wastewater treatment processes have shown a promising potential in removing various types of contaminants. Synergistic effects between iron and microbes on the contaminant degradation make the role of iron beyond that of a nutritional necessity. Exploration of the synergistic mechanisms and the interactions between iron species and microbes and their metabolic products in bio‑iron systems is therefore of significant importance. Iron, including zero-valent iron, ferrous/ferric ions and iron minerals are all reported to be capable of enhancing specific contaminant removals. Although the main role of different iron species in stimulating biological process may differ between each other, their similar transformation pathways may bring us useful information about bio‑iron systems. In this paper, an overview of iron-assisted biological wastewater treatments, including anaerobic digestion, S and Cl reduction, N and P removal, heavy metal immobilization, aromatic and halogenated hydrocarbon compounds degradation, and sludge granulation is provided. Also, the potential synergistic effects between iron and microbes involved in these processes are explored. Furthermore, the main advantages, limitations, and challenges for the development of iron-assisted treatment processes are envisaged. •Iron-assisted biological wastewater treatment processes are summarized.•Synergistic effects between iron and microbes in bio‑iron systems are highlighted.•Mechanisms behind the iron-enhanced bio-treatment are described.•Concerns on the full-scale application of iron-assisted bio-treatment are discussed.•Potential developments beyond iron-assisted bio-treatment are envisaged.